The Income and Tax Share of Very High-Income Households, 1960–1995 - Feenberg, Daniel R; Poterba, James M (American Economic Review, 2000)
This paper presents new information on the fraction of adjusted gross income, and of wages and salaries, that is reported by taxpayers in the top one half of one percent of the income distribution. This corresponds to roughly five hundred thousand households in the late 1990s. This paper relies on data from the Treasury's Individual Income Tax Model for the period 1960-1995. The definition of adjusted gross income is standardized, so that changes in the tax law do not affect the measured concentration of AGI. The results suggest that the share of AGI reported by the highest income households increased significantly between the early 1980s and the mid-1990s, with most of the increase taking place in the years immediately following the Tax Reform Act of 1986. While we find some evidence of transitory changes in the concentration of income around major tax changes, which may be the result of income retiming by high income taxpayers, re-timing does not seem to explain most of the changes since 1986.